STRATEGI PELAKU WISATA DALAM MENINGKATKAN EKONOMI LOKAL BERBASIS ISLAM DI DAERAH KEMUNING - Fitri Agus Suprianto; Iin Emy Prastiwi; Muhammad Tho’in (ITB AAS INDONESIA Surakarta, 2026)
This research was conducted in Kemuning Village, Ngargoyoso District, Karanganyar Regency, Central Java, which is developing as an Islamic-based tourism destination supported by the natural potential of the slopes of Mount Lawu. This study aims to analyze the strategies of tourism actors in enhancing the Islamic-based local economy and to identify the supporting factors and their impact on community welfare. A descriptive qualitative approach was employed, with data collection techniques including interviews, observation, and documentation. The novelty of this research lies in the analysis of integrating the Resource Support Strategy with Islamic-based tourism principles through collaboration among BUMDes (Village-Owned Enterprises), MSMEs, and local transportation service providers. The results indicate that destination development is achieved by providing Muslim-friendly facilities, such as worship facilities and halal culinary options, as well as optimizing natural resources and community participation. Successful implementation is supported by natural attractions, adequate accessibility, and synergy among stakeholders. The resulting impacts include an increase in Village Original Income (PADes), job creation, the growth of local MSMEs, and the strengthening of economic practices aligned with sharia principles. This study concludes that Islamic-based tourism in Kemuning Village is capable of driving sustainable local economic growth while maintaining Islamic values in destination management.